2007
DOI: 10.1111/j.1365-2516.2007.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents of children with haemophilia – a transforming experience

Abstract: Owing to the improvements in the management of haemophilia, children with severe haemophilia in the United Kingdom have very different experiences of their condition compared with many adults' early experiences of haemophilia. However, haemophilia can still have physical and social effects which can impact on the quality of life, not only for a child who has the condition, but also for their parents. The purpose of this study was to undertake a qualitative exploration of the impact of haemophilia on parents. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(139 citation statements)
references
References 23 publications
5
125
0
Order By: Relevance
“…So far, there has been little research on the impact of parents caring for a child with haemophilia [4]. While current qualitative assessments expose different sources of stress and emotional strains [4,6], in the present study, parents reported comparatively low psychosocial strains in a quantitative assessment. Compared to parents of children with JIA, the parents of children with haemophilia perceived less emotional burden due to their child’s illness.…”
Section: Discussionmentioning
confidence: 59%
“…So far, there has been little research on the impact of parents caring for a child with haemophilia [4]. While current qualitative assessments expose different sources of stress and emotional strains [4,6], in the present study, parents reported comparatively low psychosocial strains in a quantitative assessment. Compared to parents of children with JIA, the parents of children with haemophilia perceived less emotional burden due to their child’s illness.…”
Section: Discussionmentioning
confidence: 59%
“…Our findings revealed that carrier mothers experience challenges with treatment both in the home environment and in contact with the healthcare system. In the home setting, parents must learn to identify bleeds and administer factor treatment intravenously and gain confidence in their expertise and skills . Inserting a cannula in your child can, no matter how good ones skills are, be a stressful experience.…”
Section: Discussionmentioning
confidence: 99%
“…Caring for a child with haemophilia can cause caregiver burden through personal sacrifice, financial impacts, emotional stress and impaired health status of the caregiver . The caregiver may have to give up work to care for their child, at least during the years following diagnosis . They may also need to attend regular hospital appointments, which can be time‐consuming and financially burdensome.…”
Section: Introductionmentioning
confidence: 99%